Tissue Oximetry as a Potential Alternative to Indocyanine Green (ICG) Perfusion Assessment in Colorectal Anastomotic Cases. Issue 2 (20th April 2023) - Gonzalez-Jacobo, Alexander; Chandler, Paul; Martz, Joseph; Sherwinter, Danny
Abstract : Introduction: Anastomotic margin tissue perfusion is recognized as critical to successful colorectal anastomosis creation. Near-infrared (NIR) fluorescence imaging with indocyanine green (ICG) is the most common modality used by surgeons as an adjunct to clinical assessment in confirming the adequacy of tissue perfusion. Tissue oxygenation as a surrogate for tissue perfusion has been described in a variety of surgical specialties but its use in colorectal surgery has been limited. Here, we report our experience using a handheld tissue-oxygen meter, IntraOx, for the evaluation of colorectal tissue bed oxygen saturation (StO2 ) and compared its utility with NIR-ICG in identifying the viability of colonic tissue before anastomosis in a range of colorectal procedures. Materials and Methods: This was an institutional review board–approved multicenter trial consisting of 100 patients undergoing elective colon resections. After specimen mobilization, a clinical margin was chosen based on the oncologic, anatomic, and clinical assessment as per the clinicians' standard technique. The IntraOx device was then used to take a baseline reading of colonic tissue oxygenation on a normal segment of perfused colon. Following this, measurements were taken circumferentially at 5 cm intervals along the bowel proximally and distally to the clinical margin. A StO2 margin was then determined based on the point at which the StO2 dropped off by ≥10 percentage points. This was then compared with the NIR-ICG margin using the Spy-Phi system. Results: StO2 was found to have a sensitivity and specificity of 94.8% and 93.1%, respectively, and a positive predictive value and negative predictive value of 93.5% and 94.5%, respectively when compared with NIR-ICG. At the 4-week follow-up, no significant complications or leaks were reported. Conclusions: The IntraOx handheld device was found to be similar to NIR-ICG in identifying a well-perfused margin of colonic tissue while having the added benefits of high portability and reduced costs. Further studies looking at the effect of the IntraOx on preventing colonic anastomotic complications such as leak and stricture are warranted.